Toward SDG's 8: How sustainability livelihood affecting survival strategy of woman entrepreneurs in Indonesia - Achsania Hendratmi; Marhanum Che Mohd Salleh; Puji Sucia Sukmaningrum; Ririn Tri Ratnasari (World Development Sustainability)
The United Nations certified the Sustainable Development Goals (SDGs) in 2015. The Sustainable Development Goals (SDGs) emphasise the crucial and multifaceted contribution the business sector can make to their achievement. This study analyses sustainable livelihood models as potential solutions that could aid in attaining the SDGs. This research aimed to examine women entrepreneurs' access from the perspective of Sustainable Livelihoods, specifically focusing on business strategies based on volatility, uncertainty, complexity, and ambiguity. The study used a quantitative method to identify five components of sustainable livelihood strategies that women entrepreneurs in Indonesia have developed in response to the uncertainties brought about by the COVID-19 pandemic using Partial Least Square (PLS). The data in this study were obtained by administering a survey that utilised a structured questionnaire. The participants in this research were female entrepreneurs who had been actively operating their enterprises for an average duration of three years. The study's sample size consisted of 168 participants. The theoretical framework adopted for this study encompassed sustainable livelihoods and business strategies for survival. This study emphasises the significance of comprehending the behavioural patterns of women entrepreneurs during periods of uncertainty and demonstrates that the contextual factors of a country play a crucial role. The study recommends increasing government funding towards training small and medium-sized enterprise (SME) proprietors. This should prioritise enhancing accessibility to training opportunities, fostering networking initiatives, facilitating financial resources, and promoting company development. Additionally, the study emphasises the importance of implementing suitable government support programmes to address these areas of concern effectively.